2010
DOI: 10.1111/j.2042-7174.2010.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing a trigger tool as a method of detecting harm from medication errors in a UK hospital: a pilot study

Abstract: Although we identified some ADEs using the trigger tool, more work is needed to further refine the trigger tool to reduce the false positives and increase sensitivity. To comprehensively identify preventable ADEs, retrospective health record review remains the gold standard and we found no efficiency gain in using the trigger tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 22 publications
(61 reference statements)
6
55
0
3
Order By: Relevance
“…A recent study from the United Kingdom reported that the Global Trigger Tool has a limited ability to detect medical errors and may not be an attractive alternative to record review. 22 There is a consensus that no "gold standard" exists for the detection and classification of medical errors. The selected approach is often determined by the users' constraints and purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from the United Kingdom reported that the Global Trigger Tool has a limited ability to detect medical errors and may not be an attractive alternative to record review. 22 There is a consensus that no "gold standard" exists for the detection and classification of medical errors. The selected approach is often determined by the users' constraints and purposes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have compared the 3 main methods of detecting medical errors: voluntary reporting of sentinel events as mandated by oversight bodies, the commonly used AHRQ' s Patient Safety Indicators or other methods based on administrative discharge ICD-CM codes, and the newer Global Trigger Tool that uses specific methods for reviewing medical charts that lead to further investigation to confirm medical errors. [21][22][23][24] Voluntary reporting and administrative databases were found to underestimate medical errors. 23 Although the Global Trigger Tool seems to capture more medical errors than voluntary reporting and administrative discharge data based on ICD-9-CM codes, the tool's approach is too resources-intensive to be implemented nationally.…”
Section: Discussionmentioning
confidence: 99%
“…A revisão retrospectiva de prontuários é outra abordagem para identificar EAM; en tretanto, tem o inconveniente de demandar, em excesso, tempo e recursos humanos 7 . Como estratégia a ser massificada, pode não ser viável para monitorar a prática assistencial 8 12,13 . O objetivo do artigo é oferecer elementos para o emprego de rastreadores na vigilância dos eventos adversos a medicamentos em hospitais, apresentando o processo de apli cação de uma lista de rastreadores, assim como o desempenho de cada um deles, em um hospital público geral.…”
Section: Introductionunclassified
“…Using signs, or triggers, is a recent approach, and they act as clues in identifying adverse events and are used within hospitals, both prospectively 5 and retrospectively, 10 in intervention studies 6 or in the emergency services. 22 ADE have been shown to be promising in a variety of environments and using different approaches.…”
mentioning
confidence: 99%